Analisis dan Visualisasi Data Penjualan Menggunakan Tableau untuk Mendukung Keputusan Strategis (Studi Kasus: PT Aspirasi Hidup Indonesia Tbk) - Indah Rizki, Elvina; Anastasya Safitri, Adinda; Servanda, Yustian; Sudinugraha, Tri (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2025)
This research aims to analyze and visualize sales data using Tableau as a Business Intelligence tool to support strategic decision-making at PT Aspirasi Hidup Indonesia Tbk. The background of this study lies in the increasing need for effective data visualization to interpret complex sales information. A descriptive quantitative method was employed using secondary data from the company’s 2023 annual report and simulated sales transaction data. The data were visualized in Tableau through three main dashboards: monthly sales and profit trends, product category performance, and customer segment analysis. Results show that the Lifestyle product category and Corporate customer segment contributed the highest sales and profits. February and September were identified as the most profitable months. The use of Tableau enabled efficient data interpretation and quick decision-making insights. This study highlights the significance of visual-based analytics in improving corporate strategy, and suggests further research using larger datasets and predictive models for broader analysis.